Investigation of wound healing activity of the flavonoid schaftoside isolated from Lychnis chalcedonica - Tatiana N. Povetyeva; Olga G. Afanasyeva; Larisa N. Zibareva; Yulia V. Nesterova; Nikolay I. Suslov; Pavel V. Kulpin; Gleb N. Zyuz`kov; Svetlana G. Krylova; Olesya V. Vsyakikh (Research Results in Pharmacology, 2023)
Introduction: This article studies the wound healing activity of the flavonoid schaftoside – apigenin -6-C-β-D glucopyranosyl 8-C-α-L arabinopyranoside (C26H28O14) isolated from the above-ground part of Lyсhnis chalcedonica L.